2013
DOI: 10.3892/ijo.2013.1941
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of EGFR and c-Met kinase activation by MJ-56 reduces metastasis of HT29 human colorectal cancer cells

Abstract: Quinazolinone derivatives are known to possess anticancer activities on cell metastasis and cell death in different human cancer cell lines. Here, we studied the anti-metastasis activity and the underlying mechanisms of the novel quinazoline derivative MJ-56 (6-pyrrolidinyl-2-(3-bromostyryl)quinazolin-4-one). MJ-56 inhibited cell migration and invasion of HT29 human colorectal cancer cells by wound-healing and Matrigel-coated transwell assays in a concentration-dependent manner. MJ-56-treated cells resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…In line with our findings, downregulation of p-rpS6 are also attenuated the cells invasion in esophageal squamous cell carcinoma [ 18 ] and renal angiomyolipoma [ 7 ]. MJ-56, a new novel anti-metastasis drug, even showed the p-rpS6-mediated invasion inhibition effects in colorectal cancer cells [ 53 ]. These results imply that p-rpS6 might be importantly involved in multiple cells invasion and its overexpression will probably facilitate the tumors aggressiveness to a large extent.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, downregulation of p-rpS6 are also attenuated the cells invasion in esophageal squamous cell carcinoma [ 18 ] and renal angiomyolipoma [ 7 ]. MJ-56, a new novel anti-metastasis drug, even showed the p-rpS6-mediated invasion inhibition effects in colorectal cancer cells [ 53 ]. These results imply that p-rpS6 might be importantly involved in multiple cells invasion and its overexpression will probably facilitate the tumors aggressiveness to a large extent.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that cell metastasis is one of the major causes of colorectal cancer-related mortality (17,18,30). Interference with human epidermal growth factor receptor (EGFR) or downstream intracellular signaling provides a novel approach in cancer chemotherapeutic agents (31)(32)(33). Activation of the EGFR pathway promotes by EGF-stimulated responsible for colorectal cancer cell growth, invasion, metastasis and inhibition of cell death (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…They have proven that MJ‐56 can inhibit invasion and migration of HT29 cells by targeting EGFR and c‐MET, and therefore ERK and PI3K/AKT/mTOR signaling. The blocking of matrix metalloproteinases is due to inhibition of the NF‐kB signaling pathway . Hu et al used curcumin on DU145 cell lines, and have shown that curcumin can suppress HGF‐induced effects that included upregulation of vimentin and downregulation of E‐cadherin.…”
Section: The Therapeutic Targeting C‐met/hgf Signaling Pathway In Crcmentioning
confidence: 99%